Brain neurons internalise polymeric micron-sized capsules: Insights from in vitro and in vivo studies - Olga Kopach; Olga A. Sindeeva; Kaiyu Zheng; Eleanor McGowan; Gleb B. Sukhorukov; Dmitri A. Rusakov (Materials Today Bio)
Nanoengineered encapsulation presents a promising strategy for targeted drug delivery to specific regions in the body. While polyelectrolyte-based biodegradable microcapsules can achieve highly localised drug release in tissues and cell cultures, delivering drugs to intracellular sites in the brain remains a significant challenge. In this study, we utilized advanced imaging techniques, both in vitro and in vivo, to investigate whether brain neurons can internalise polyelectrolyte-based microcapsules designed for drug delivery. High-resolution live-cell imaging revealed that differentiating N2A cells actively internalise microcapsules, often incorporating multiple capsules per cell. Likewise, primary hippocampal and cortical neurons were observed to effectively internalise polymeric microcapsules. In the intact brain, multiplexed two-photon excitation imaging in vivo confirmed the internalisation of microcapsules by cortical neurons following delivery to the somatosensory brain region. This internalisation was time-dependent, correlated with particle size and mediated by a macropinocytosis mechanism that appears to bypass lysosomal formation. Importantly, the presence of internalised microcapsules did not impair neuronal function, as neurons maintained normal firing activity and action potential characteristics. Furthermore, no adverse effects were observed after a week of microcapsule presence in the mouse brain. Our findings indicate that polymeric microcapsules are effective and safe carriers for intracellular drug delivery to brain neurons, providing a targeted approach with potential therapeutic applications.